Classification of edible oils by using time domain NMR (TD-NMR) technique and microwave (MW) dielectric spectroscopy - (:unkn) unknown (My University, 2023)
Increasing worldwide food demand as a result of the increasing population has led to an increase in vegetable oil prices. Olive oil, one of the most popular edible oils, is regrettably commonly adulterated by the addition of a different, less expensive oil to lower its price. As a result, many processes are carried out on edible and olive oil is one of the most cheated products today. Microwave dielectric technique (MW), in parallel with Time Domain Nuclear Magnetic Resonance (TD-NMR) technique, has started to be used in food analysis because it can analyze the content of the product, which cannot be distinguished by sensory characteristics in a simple, fast and high-efficiency way.In this study, spin–lattice (T1) and spin–spin (T2) relaxation times of edible oils were measured. Dielectric permittivity constants Ɛ1 and Ɛ2 have also been measured from 10 MHz to 20 GHz. It is observed that spin–spin (T2) and spin–lattice (T1) relaxation times of pure olive oil are shorter than those of sunflower oil and that T1 and T2 are shorter for riviera olive oils than for extra virgin olive oils. It was found that the T1 and T2 values increased with the increase in temperature in the measurements based on the investigation of the impact of temperature on the relaxation times. The highest Ɛ1 values are found in sunflower oils, while the lowest Ɛ1 values are found in riviera olive oil. As is well known, the amounts of oleic and linoleic acid in edible oils also affect the T1-T2, viscosity, and Ɛ1-Ɛ2 values. As a result, relaxation times and dielectric parameter constants are used to categorize and distinguish edible oils, particularly extra virgin and riviera olive oils.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Kimya; Analitik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Agricultural Sciences; Agriculture; Food Engineering; Life Sciences; Biotechnology; Chemistry; Analytical Chemistry; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Tarım Bilimleri; Mühendislik; Mikrobiyoloji; Sosyal Bilimler Genel; GIDA BİLİMİ VE TEKNOLOJİSİ; KİMYA, ANALİTİK; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; MÜHENDİSLİK, İMALAT; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); Social Sciences (SOC); AGRICULTURAL SCIENCES; ENGINEERING; CHEMISTRY; MICROBIOLOGY; SOCIAL SCIENCES, GENERAL; FOOD SCIENCE & TECHNOLOGY; CHEMISTRY, ANALYTICAL; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; ENGINEERING, MANUFACTURING; Fizik Bilimleri; Yemek bilimi; Uygulamalı Mikrobiyoloji ve Biyoteknoloji; Emniyet, Risk, Güvenilirlik ve Kalite; Güvenlik Araştırması; Sosyal Bilimler ve Beşeri Bilimler; Physical Sciences; Food Science; Applied Microbiology and Biotechnology; Safety, Risk, Reliability and Quality; Safety Research; Social Sciences & Humanities; Dielectric Constants; Edible Oil; Relaxation Time; TD-NMR